Do High Birth Rates Hamper Economic Growth? - Li, Hongbin; Zhang, Junsen (The Review of Economics and Statistics, 2007)
This paper examines the impact of the birth rate on economic growth by using a panel data set of 28 provinces in China over twenty years. Because China's one-child policy applied only to the Han Chinese but not to minorities, this unique affirmative policy allows us to use the proportion of minorities in a province as an instrumental variable to identify the causal effect of the birth rate on economic growth. We find that the birth rate has a negative impact on economic growth. The finding not only supports the view of Malthus, but also suggests that China's birth control policy is indeed growth enhancing.